Instrumental music in an age of sociability : Haydn, Mozart and friends - Sutcliffe, W. Dean (Cambridge University Press, 2023)
"Sociability may be a key term of reference for eighteenth-century studies as a whole, but it has not yet developed an especially strong profile in music scholarship. Many of the associations that it brings do not fit comfortably with a later imperative of individual expression. W. Dean Sutcliffe invites us to face up to the challenge of re-evaluating the communicative rationales that lie behind later eighteenth-century instrumental style. Taking a behavioural perspective, he divides sociability into 'technical' and 'affective' realms, involving close attention both to particular recurring musical patterns as well as to some of the style's most salient expressive attributes. The book addresses a broad span of the instrumental production of the era, with Haydn as the pivotal figure. Close readings of a variety of works are embedded in an encompassing consideration of the reception of this music"--